E-Commerce: An essential lever for regional integration in Africa - Rahul Bhatnagar; Julien Gourdon (Fondation pour les études et recherches sur le développement international (FERDI), 2025)
E-commerce has become an essential element, rather than a mere option, for various growth drivers in Africa. The adoption by the African Union of the e-commerce strategy in June 2024 and then of the AfCFTA e-commerce protocol on February 15th 2025 are important milestones for the digital commerce revolution in Africa and its role in regional integration. In this policy brief we will take a closer look to this two initiatives as well as to the challenges to be met.
Keywords: 330; Digital technologies; AfCFTA